THE RELATIONSHIP BETWEEN PEER SOCIAL SUPPORT AND SUBJECTIVE WELFARE IN VIEW OF GENDER OF VOCATIONAL HIGH SCHOOL STUDENTS - Lijma Uliana Ritonga; Nefi Darmayanti; Suaidah Lubis (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
The purpose of this study was to determine the relationship between peer social support and subjective well-being in terms of the gender of SMK students in Tanjung Morawa. In this study using an explanatory quantitative approach. A sample of 192 based on random sampling technique. Using two psychological scales, namely the scale of subjective well-being and peer social support. In processing the data used normality test, linearity test, and hypothesis testing. The results showed that there was a significant relationship between peer social support and students' subjective well-being. The higher the peer social support, the higher the subjective well-being, and vice versa. There is no significant difference in subjective well-being between male and female students. This states that both male and female students have the same level of subjective well-being. It is hoped that the school can improve the subjective well-being of students by increasing the social support of students' peers, through entering the community they want, providing space to talk to friends, holding school vent events and other activities. Students are expected to be able to improve subjective well-being by: getting involved in school sharing events, communicating feelings and emotions in various situations such as feeling pleasant, having positive expectations in the learning process, entering the community they want. It is hoped that the school can improve the subjective well-being of students by increasing the social support of students' peers, through entering the community they want, providing space to talk to friends, holding school vent events and other activities. Students are expected to be able to improve subjective well-being by: getting involved in school sharing events, communicating feelings and emotions in various situations such as feeling pleasant, having positive expectations in the learning process, entering the community they want. It is hoped that the school can improve the subjective well-being of students by increasing the social support of students' peers, through entering the community they want, providing space to talk to friends, holding school vent events and other activities. Students are expected to be able to improve subjective well-being by: getting involved in school sharing events, communicating feelings and emotions in various situations such as feeling pleasant, having positive expectations in the learning process, entering the community they want.